Financial development, rule of law and wealth inequality: Bayesian model averaging evidence - Roman Horváth; Eva Horvatovay; Maria Siranova (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2017)
We examine the determinants of financial development using our global sample and employing a rich set of measures of financial development that assess the degree of depth, access, stability and efficiency of financial intermediaries. We use Bayesian model averaging to test competing theories within this unifying framework. Examining nearly 40 potential determinants of financial development, we find that the rule of law and the level of economic development are the most important. Wealth inequality is irrelevant for banking sector development but positively associated with stock market development. Finally, our results suggest that financial market regulations matter for stock market efficiency and financial stability.
urn:nbn:de:101:1-2018061908101396073086
Keywords: G10; G20; 330; financial development; Bayesian model averaging; rule of law; wealth inequality